2002
DOI: 10.1093/brain/awf274
|View full text |Cite
|
Sign up to set email alerts
|

The proteasome is a major autoantigen in multiple sclerosis

Abstract: Multiple sclerosis seems to be an autoimmune disease of unknown aetiology affecting the white matter of the CNS. It is generally accepted that the autoimmune response is directed against specific components of myelin. We show here that proteasome, a ubiquitous protease complex composed of 14 different subunits, is a target for autoantibodies (IgG and IgM classes) present in the serum (66%, 73 out of 110) and in the CSF (61%, 16 out of 26) of patients with multiple sclerosis. Using recombinant proteasomal subun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 33 publications
0
32
0
2
Order By: Relevance
“…Further studies will show, whether similar to cproteasomes in blood serum and bronchoalveolar fluid, the concentration of extracellular proteasomes in CSF changes under pathological conditions. This is especially interesting since neuroinflammation, e.g., multiple sclerosis, and neurodegeneration like Alzheimer's and Parkinsons disease, have been reported to go along with or may even be due to changes in the ubiquitin proteasome system (Keller and Markesbery 2000;Mayo et al 2002;Olanow and McNaught 2006;Beyer et al 2007;Gillardon et al 2007;Thuy-Tien et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies will show, whether similar to cproteasomes in blood serum and bronchoalveolar fluid, the concentration of extracellular proteasomes in CSF changes under pathological conditions. This is especially interesting since neuroinflammation, e.g., multiple sclerosis, and neurodegeneration like Alzheimer's and Parkinsons disease, have been reported to go along with or may even be due to changes in the ubiquitin proteasome system (Keller and Markesbery 2000;Mayo et al 2002;Olanow and McNaught 2006;Beyer et al 2007;Gillardon et al 2007;Thuy-Tien et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These antigens include a,β-crystallin (72), heat-shock proteins (73), transaldolase (74,75), proteasomes (76), and DNA (77). Other studies found no increased responses in MS patients or disease specificity for several of these autoantigens (78,79).…”
Section: 24mentioning
confidence: 99%
“…The 20S proteasome had been identified as a target of the humoral autoreactive immune response [11] and a major autoantigen in MS patients [12]. The proteolytic activities of proteasomes are reduced in brain tissue of MS patients [13].…”
mentioning
confidence: 99%